Об’єктивація концепту RISIKO фразеологічними конструкціями „koste es, was es wolle“, „(es) komme, was (da) wolle“ - Застровська, Софія Олександрівна; Zastrovska, S. O. (Волинський національний університет імені Лесі Українки, 2009)
У статті розглядаються фразеологічні конструкції „koste es, was es wolle”, „(es) komme, was (da) wolle“ як засоби об’єктивації концепту RISIKO (РИЗИК); виявляються варіативні модифікації зазначених конструкцій та умови їхньої руйнації. The article deals with the analysis of the phraseological constructions „koste es, was es wolle”, „(es) komme, (was) da wolle“ as means of objectivization of the concept RISIKO (RISK). The variable modifications of the given constructions and the conditions of their destroying are suggested.
Objectivization of Сoncept of RISIKO by the Phraseology Constructions of “koste es, was es wolle” “(es) komme, was (da) wolle”
Keywords: концепт; засоби; конфігурації концептів; модифікація; concept; means of objectivization; concept configurations; modifications